The Cognitive Control Model of Work-related Flow - Weintraub, Jared; Nolan, Kevin P.; Sachdev, Aditi Rabindra (Frontiers in Psychology, 2023)
Although several models of flow have been proposed that include environmental and trait-based antecedents of the state, elements of cognitive control that enable workers to experience flow and its subsequent outcomes at work have largely been overlooked. This research proposes and provides empirical support for the "Cognitive Control Model of Work-related Flow," which integrates antecedents of work-related flow related to the ability to focus concentration of cognitive resources towards experiencing flow at work. As such, along with flow at work, the model includes the antecedents of grit, flow metacognition, and mindfulness at work, and the outcomes of work performance, engagement, and burnout. Findings across three studies (a cross-sectional, a time-lagged, and a one-day experience sampling method study) utilizing MTurk participants provided support for the model, as grit, mindfulness, and flow metacognition predicted flow, and flow predicted subjective performance, engagement, and burnout. Theoretical implications and the potential for developing flow interventions at work are discussed.